Using an Asteraceae checklist to understand collection history, species density and conservation implications: a case study in the state of Alagoas, Northeastern Brazil - Soares, Gleison; Roque, Nádia; Alves, Fábio Vitalino Santos; Amorim, Vivian Oliveira; Barbosa, Maria Liris; Guterres, Aryana Vasque Frota; Alves, Maria; Loeuille, Benoît (Phytotaxa, 2022)
Alagoas is a Brazilian state contained in the area of two large and important phytogeographic domains: Atlantic Forest and Caatinga. Although the presence of these domains possibly indicates a considerable biodiversity, floristic studies in the state are still scarce, especially for the family Asteraceae. In this sense, we developed a combined GIS and floristic study approach to highlight aspects associated with the diversity, distribution and conservation of Asteraceae in Alagoas. Thus, the aims of this paper are to: (1) present a checklist of Asteraceae in the state of Alagoas, (2) provide an overview of areas with highest species richness and collection density, and (3) verify the representativeness of the group in conservation units within the state. Asteraceae is represented in Alagoas by 112 species, 35 genera and 12 tribes. Among them, 51 species are new state records, with Lepidaploa (Cassini) Cassini and Mikania Willdenow having the highest number of new occurrences. Our results indicate that collection density and species richness within the state are strongly correlated and concentrated mainly in the Atlantic Forest domain. On the other hand, the least sampled areas correspond to the Steppic Savanna (caatinga vegetation) and the Dense Ombrophilous Forest, which we indicate as in need of increased Asteraceae collection efforts. 42% of the species do not have records included in Protected Areas, and of the 58% that do, most correspond to taxa widely distributed in Brazil or that are considered ruderal, leaving out rarer species with restricted habitats or evaluated as being at risk.